The threats of small-sided soccer games: A discussion about their differences with the match external load demands and their variability levels - Clemente, F. M. (Strength and Conditioning Journal, 2020)
Small-sided games (SSGs) are regularly used in soccer training. SSGs are used because of their capacity to replicate the demands of a real match or control the overall workload of players. However, some threats may result from the use of SSGs. Thus, it is important to highlight those threats to improve the effectiveness of SSG implementation. Based on that, we examine and discuss comparisons between external load SSGs and real-game scenarios, the intra- and interplayers physical variability during the smaller formats of play, the consequences of SSGs in terms of the proper physical stimulation of players, and injury prevention